Making peace : a first-hand account of the Arab-Israeli peace process - Bentsur, Eytan (Praeger, 2001)
An insider's account of the origins of the Middle East peace process at the Madrid Peace Conference in 1991. Bentsur sheds new light on the leading personalities and ideas that made the conference a success and a foundation for future progress.